PROJECT MANAGEMENT METHODOLOGY OF THE ENTERPRISE (Development Service Industry Management, 2024)
Project management solves many problems in various areas of business and ensures effective performance of tasks, which allows you to achieve success and meet the requirements of a competitive market. Project activity at the enterprise involves the implementation of specific projects in order to achieve the strategic goals of the enterprise. In our opinion, a project should be understood as a temporary and organized activity aimed at achieving a specific goal or result with limited resources and time. Project activity is a specific type of activity aimed at solving a specific problem, performing a task or achieving a certain goal with the help of organizational efforts and resources. The main features of project activities include: goal orientation, limited time and resources, organizational approach, uniqueness, controllability. The implementation of project activities at the enterprise can be carried out by various methods, depending on the specific needs and features of the project. Therefore, the article examines the main methods of implementing project activities at the enterprise by the years of their origin, namely: the critical path method with software on a UNIVAC computer (1967), the PERT network planning system (1957–1958), pre-project analysis ( 1956–1958), GERT system (new generation of network models) (1966), grid planning (1970), organization of work on the project (1975), system project planning (1980), restructuring methods of the project (1980), configuration and change management methods (1985), quality management methods in the project (1985), system management of functions and subsystems (1985), quality management "six sigma" (1986 ), the PRINCE (Projects in Controlled Environments) project management methodology (1989), risk management methods (1990), the use of Microsoft Project by practitioners (1991), a framework for developing and managing projects on the basis of flexibility (Scrum) (1993), project team formation methodology (1995), project management methodology PMBOK (Project Management Body of Knowledge) (1996), project management methodology PRiSM (Projects Integrating Sustainable Methods) (2000), model maturity of project management (2002), project management method based on visual control (Kanban) (2004), total cost management system (Total Cost Management Framework) (2006).
Keywords: project; project management; project activity; methods of implementation of project activity